2008
DOI: 10.1523/jneurosci.0860-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Mode of Membrane Fusion Dependent on Tight SNARE Zippering

Abstract: SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins have a key role in membrane fusion. It is commonly assumed that pairing of SNARE proteins anchored in opposing membranes overcomes the repulsion energy between membranes, thereby catalyzing fusion. In this study, we have increased the distance between the coiled-coil SNARE motif and the transmembrane domain of the vesicular SNARE synaptobrevin-2 by insertion of a flexible linker to analyze how an increased intermembrane dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 36 publications
(47 reference statements)
7
35
1
Order By: Relevance
“…However, the augmentation of the granular content could be a result of compound fusion (i.e., two or more SG that fuse before exocytosis) (50). Previous analysis of amperometric spikes has indicated that different modes of exocytosis could be reflected in several characteristics, such as the spike half-width or spike rise (39,51,52). Moreover, a previous study suggested that amperometric feet correspond to SG with higher content (35), similar to what we observed in our study (Table II).…”
Section: Discussionsupporting
confidence: 90%
“…However, the augmentation of the granular content could be a result of compound fusion (i.e., two or more SG that fuse before exocytosis) (50). Previous analysis of amperometric spikes has indicated that different modes of exocytosis could be reflected in several characteristics, such as the spike half-width or spike rise (39,51,52). Moreover, a previous study suggested that amperometric feet correspond to SG with higher content (35), similar to what we observed in our study (Table II).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the kinetics of exocytosis are markedly altered by the linkers between the SNARE motif and the TMDs of VAMP (66,136,217,316,406) and syntaxin (668), and by the linker between the two SNARE motives in SNAP25 (69,436). Thus the linker regions outside the SNARE motif play an important role in the kinetics of membrane fusion mediated by SNAREs, in line with the idea that SNARE assembly can be induced up to the transmembrane regions (613).…”
Section: Different Trans-snare Statesmentioning
confidence: 75%
“…Exocytosis of LDCVs containing a brain-derived neurotrophic factor (BDNF) is full fusion in dendrites and kiss-and-run fusion in axons (397). SNAREs, and many SNARE-interacting proteins, including Munc18a (173,292), synaptotagmins (579,742), Doc2 (178), SNAP25 (163,436), VAMP2 (66,316), syntaxin (227), SNARE complex (226), and complexin (9,17), affect fusion pore properties (see sect. V).…”
Section: How Does the Fusion Pore Open?mentioning
confidence: 99%
“…Multiple studies suggest that in addition to the SNARE motifs of synaptobrevin-2, syntaxin-1, and SNAP-25 that mediate SNARE-complex formation, the transmembrane regions (TMRs) of synaptobrevin-2 and syntaxin-1 are essential for membrane fusion and may induce fusion-pore opening (Han et al, 2004; Xu et al, 2005; Deák et al, 2006; Kesavan et al, 2007; Bretou et al, 2008; Lu et al, 2008; Stein et al, 2009; Fdez et al, 2010; Guzman et al, 2010; Ngatchou et al, 2010; Risselada et al, 2011; Shi et al, 2012). In yeast, replacement of the TMR of the synaptobrevin homolog Snc1p with a geranylgeranyl anchor not only blocked membrane fusion during exocytosis, but even transformed Snc1p into an inhibitor of exocytosis (Grote et al, 2000).…”
Section: Introductionmentioning
confidence: 99%